Belmiro Borba, um homem de abismos: um personagem em conflito sob o prima da melancolia na obra O amanuense Belmiro, de Cyro dos Anjos - Souza, Keynesiana Macêdo (2015)
This master‘s thesis presents an analytical reading of Cyro dos Anjos (1906-1994)‘s novel O amanuense Belmiro (1937) and its main objective is to analyze the way some aspects of melancholy, together with the notion of memory, diary writing as well as time permeate all the narrative of this unique book in the Brazilian literary scenario. Anjos‘ novel is an atypical work in the fiction of the 1930s as it is considered a dissonant voice compared to the regional and social productions of the time it was published. Among other themes, the book depicts the relationship of man with life; the present and the past; love and frustrations and the hero in search of itself. Belmiro Borba, character-narrator, is a sentimental man, often handicapped by his inner life. For this matter, Borba decides to write a book in order to register his stories, memories, feelings, meditations and illusions. From this perspective, this research aims to deal with issues related to the aesthetics of melancholy, especially its relationship with the creative process, which belongs to Borba‘s attempt to write literature. Throughout our academic research, we used the work of Aristotle (1998), Lambotte (2000), Benjamin (2011) and Kristeva (1989) to articulate relevant issues of melancholy; Halbwachs (2006) on the concept of memory, among other theorists who were essential to the completion of this study.